Image, Appearance and Vanity in the Use of Media Spaces and Videoconference Systems - Filo, Jose Eurico de Vasconcelos; Inkpen, Kori; Czerwinski, Mary (International ACM conference on Supporting group work (Group 2009), 2009)
Media spaces and videoconference systems are beneficial for connecting separated co-workers and providing rich contextual information. However, image sharing communication tools may also touch on sensitive spots of the human psyche related to personal, perceived image issues (e.g., appearance, self-image, self-presentation and vanity). We conducted two user studies to examine the impact of self-image concerns on the use of media spaces and videoconference systems. Our results suggest that personal, perceived image concerns have a considerable impact on the comfort level of users and may hinder effective communication [8]. We also found that image filtering techniques can help users feel more comfortable. Our results revealed that distortion filters, which are frequently cited to help preserve privacy, do not tend to be the ones preferred by users. Instead, users seemed to favor filters that make subtle changes to their appearance, or, in some instances, they preferred to use a surrogate instead.